Who Wants Collective Bargaining Any Way? - Carrothers, A. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
Collective bargaining in Canada is undergoing strains today, as it has in different circumstances, which are challenging the process and are causing responsible people to question whether it can be improved or should be replaced.